과민대장증후군 환자의 증상의 중증도와 식습관 및 증상유발식품과의 관련성 - 백주연; 전상은 (Journal of Korean biological nursing science, 2015)
Purpose: The purpose of this study was to investigate eating habits and the frequency of trigger-food consumption in patients with irritable bowel syndrome (IBS) and to examine the associations of these variables with IBS symptom severity. Methods: We included 145 ROME III-positive IBS patients (mean age 31.2 years, 73.8% of female). Subjects completed an eating-habits and food-consumption questionnaire, IBS-Symptom Severity Scale (IBS-SSS) and Brief Symptom Inventory-18 (BSI-18) for psychological distress. Results: Subjects with unhealthy eating-habits such as irregular meal times, frequently eating out and overeating tended to show higher IBS symptom severity. The severity of IBS symptoms related to the frequency of the consumption of trigger foods. Subjects who ate trigger-foods (i.e., tofu, beans, almonds, and peanuts) less frequently showed higher IBS symptom severity (p=.045, .042, .016, and .019, respectively). However, subjects who ate spicy foods, instant foods, and noodles more frequently experienced more severe IBS symptoms (p=.018, .011, and .023 respectively). Conclusion: This study showed that IBS symptom severity was related to meal intake patterns and frequency of trigger food consumption. These findings could provide a basis for developing an intervention program for IBS patients.